Baalbek, Libanon. Forschungen im Steinbruch, Konservierungsprojekt im Bustan Nassif und Aufarbeitung der Arbeiten 2001 bis 2012. Die Arbeiten des Jahres 2016 - van Ess, Margarete (e-Forschungsberichte des DAI, 2017)
In Baalbek, the excavation of the Southern quarry continued and was completed. Larger parts of the area were prepared for visitors by providing tracks and securing excavated areas with retaining walls. In addition, the conservation project for the archaeological area “Bustan Nassif”, a living quarter mainly of the Ayyubid and Mameluk Periods was continued. It offers training in technics of building conservation as well as in the maintenance of archaeological architectural structures. In 2016, the conservation of the so-called Damascus Gate as well as of the remains of a mosque and a khan was completed.